Effects of Fluoride on Submandibular Glands of Mice: Changes in Oxidative Biochemistry, Proteomic Profile, and Genotoxicity - Lima, Leidiane Alencar de Oliveira; Miranda, Giza Hellen Nonato; Aragão, Walessa Alana Bragança; Bittencourt, Leonardo Oliveira; dos Santos, Sávio Monteiro; de Souza, Michel Platini Caldas; Nogueira, Lygia S.; de Oliveira, Edivaldo Herculano Corrêa; Monteiro, Marta Chagas; Dionizio, Aline; Leite, Aline Lima; Pessan, Juliano Pelim [UNESP]; et al. (Frontiers, 2021)
Although fluoride (F) is well-known to prevent dental caries, changes in cell processes in different tissues have been associated with its excessive exposure. Thus, this study aimed to evaluate the effects of F exposure on biochemical, proteomic, and genotoxic parameters of submandibular glands. Twenty one old rats (n = 30) were allocated into three groups: 60 days administration of drinking water containing 10 mgF/L, 50 mgF/L, or only deionized water (control). The submandibular glands were collected for oxidative biochemistry, protein expression profile, and genotoxic potential analyses. The results showed that both F concentrations increased the levels of thiobarbituric acid–reactive substances (TBARS) and reduced glutathione (GSH) and changed the proteomic profile, mainly regarding the cytoskeleton and cellular activity. Only the exposure to 50 mgF/L induced significant changes in DNA integrity. These findings reinforce the importance of continuous monitoring of F concentration in drinking water and the need for strategies to minimize F intake from other sources to obtain maximum preventive/therapeutic effects and avoid potential adverse effects.
Keywords: fluoride; genotoxicity; proteome; submandibular gland; toxicity